Evaluasi Operasi Tangkap Tangan KPK - Oktavianto, Rizky; Abheseka, Norin Mustika Rahadiri (Komisi Pemberantasan Korupsi, 2019)
The implementation of Sting Operation as one of the strategies implemented by the Komisi Pemberantasan Korupsi (KPK) to crack down corruption cases in Indonesia raises pros and cons. The cons believe that Sting Operation has no significant impact on eradicating corruption in Indonesia, illegal and threatening privacy. Meanwhile, the pros believe that the KPK sting operation can reveal corruption cases quick and produce concrete evidence. By using the six evaluation criteria from Dunn, this article seeks to be a mediator between the two camps by conducting evaluative studies of the implementation sting operations in the eradication of corruption in Indonesia. The author found that sting operations become intensive activities of the KPK during 2015-2018. Hand arrest operations also effective and efficient to catch the corrupter’s, as well as increasing public involvement in corruption eradication in Indonesia. However, the massive sting operations that are carried out at the national level to the regions have not yet provided significant impact on reducing corruption in Indonesia. Therefore, eradicating corruption cannot only be in terms of enforcement, but it also needs to be strengthened in the prevention side.